Suits. Season one [videorecording (DVD)] - Macht, Gabriel, 1972-; Adams, Patrick J., 1981-; Torres, Gina (Universal Studios Home Entertainment, 2012)
This new original series delves into the fast-paced, high-stakes world of a top Manhattan corporate law firm, where hotshot attorney Harvey Specter makes a risky move by hiring the brilliant but unmotivated Mike Ross as his new associate. The only problem is he doesn't have an actual law degree.